Subtitling English Speech - Nanaa, Kutiba (2009)
Human-being learn their mother tongue instinctively from the childhood, but when they grow up, many challenges will appear when they try to learn other languages. The building of vocabulary bank and understanding of grammar is not an easy job, so some people use computer to help to translate other language to their mother tongue, but this mean also got its limitation and disadvantages such as the misunderstanding of the words. In this study, the researcher will use artificial intelligent technologies to solve these problems. First, speech will be received as sound waves, then it will be segment into letters and recognized by the usage of Neural Network.